8n+13=7(n+10)

Simple and best practice solution for 8n+13=7(n+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8n+13=7(n+10) equation:


Simplifying
8n + 13 = 7(n + 10)

Reorder the terms:
13 + 8n = 7(n + 10)

Reorder the terms:
13 + 8n = 7(10 + n)
13 + 8n = (10 * 7 + n * 7)
13 + 8n = (70 + 7n)

Solving
13 + 8n = 70 + 7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-7n' to each side of the equation.
13 + 8n + -7n = 70 + 7n + -7n

Combine like terms: 8n + -7n = 1n
13 + 1n = 70 + 7n + -7n

Combine like terms: 7n + -7n = 0
13 + 1n = 70 + 0
13 + 1n = 70

Add '-13' to each side of the equation.
13 + -13 + 1n = 70 + -13

Combine like terms: 13 + -13 = 0
0 + 1n = 70 + -13
1n = 70 + -13

Combine like terms: 70 + -13 = 57
1n = 57

Divide each side by '1'.
n = 57

Simplifying
n = 57

See similar equations:

| 8x-9=4x | | 3(2X+2)-4(3X+2)=5X+20 | | (6x-3)=(4x+7) | | 2x=(360+2) | | (6)*(3x+2)=(6)*(5x-10) | | R(6x-3)=(4x+7) | | 5n-2(n-2)=-11+3n+5 | | 4y+2=8(y+7) | | 5(-9+x)=-25 | | 6(2+x)=72 | | -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 |

Equations solver categories